„pupillák nedves sivataga”: Biomateriális szemlélet és képtechnikák Vida Gergely Mellékalak című kötetében - L. Varga, Péter (Studia Litteraria, 2022)
This paper attempts an observation of Gergely Vida’s poetry, particularly his collection Mellékalak („Sideforms”), through a bare scientific understanding of life as well as through the presence of visual techniques. The biomaterial conditions of life are given meaning by cultural techniques, and vice versa: cultural techniques (and art) prefigure what is known about life. This duality gives simultaneous function to the anthropological horizon, while also leading onto the preceding (or proceeding) corporal reality.